Pengaruh Harga Dan Kualitas Produk Terhadap Kepuasan Pelanggan Produk Indihome Di PT. Telkom Medan Sumatera Utara (Studi Kasus Di Marelan) - Nelli Roida M. Hutabarat; Yahya Tanjung (Student Research Journal, 2023)
Customer satisfaction is the level of consumer feelings after comparing what he received and his expectations. A customer, if he is satisfied with the value provided by a product or service, is very likely to be a customer for a long time. This study aims to determine and analyze the effect of price and product quality on Indihome customer satisfaction at PT. Telkom Medan. This type of research is quantitative research. The type of data used is primary data and secondary data obtained from questionnaires. This research was conducted on Indihome customers with a population of 1,900 with a sample of 95 respondents who were taken by purposive sampling method with a sampling technique using the slovin formula. The analytical method used is multiple linear regression analysis. The results of the analysis show that the price and quality of the product together or simultaneously have a positive and significant effect on the dependent variable in the form of customer satisfaction for Indihome products at PT.Telkom Medan, North Sumatra. Partially price has a positive and significant effect on customer satisfaction of Indihome PT.Telkom Medan, North Sumatra, partially product quality has no positive and significant effect on customer satisfaction of Indihome PT.Telkom Medan, North Sumatra.